Reumanização no Desenho Técnico: uma análise sobre o aperfeiçoamento dos instrumentos de execução - Santana, Hemeclecio Nascimento (2025)
This research analyzes the evolution of technical drawing technologies over the past fifty years and their impacts on the dehumanization of graphic representations, especially in the identity formation of Architecture and Engineering professionals. With the advancement of digital tools, there has been a shift from manual to digital drawing, which brought benefits such as increased precision, clarity, and productivity. However, this transition also led to a detachment of the designer from the sensory and subjective experience of drawing, resulting in the loss of humanizing elements in graphic representations. The main objective is to understand how these transformations influence the creative process and the teaching of technical drawing. To this end, the adopted methodology combined a literature review with a comparative analysis of technical drawings produced by three generations of architects from the Bratke family, who used different technologies over the last five decades. The results show that manual drawings displayed gesture, unique strokes, and imperfections that revealed the author's identity and fostered a closer connection between the professional and their creation. In contrast, digital drawings demonstrate increasing standardization and a lack of subjective marks, contributing to the dehumanization of the process. The research concludes that it is necessary to critically reflect on the use of technology in the teaching and practice of technical drawing, aiming for a balance between precision and expression. The study also proposes a methodological approach that can be applied to other investigations focused on graphic analysis and the preservation of identity in technical representation.